Adaptation and Psychometric Properties of the Smartphone Dependence and Addiction Scale “EDAS” to measure addictive behaviors to the Smartphone in adolescents and young people between 18 and 35 years of the city of Puno – 2020 - Lucana Hancco, Aurora (2021)
Objective: To adapt and analyze the psychometric properties of the “Smartphone Dependence andAddiction” scale (EDAS) original authorship of María Aranda López, Virginia Fuentes Gutiérrez andMarta García Domingo, who created the instrument in 2017. Methodology: A sample of 117 peopleaged 18 to 35 years between men and women, data collection was done online through the Googleform platform, the results show that the Smartphone Dependence and Addiction Scale (EDAS),revised, it has a validity index (V = .98) from the evaluation of four evaluation criteria (Clarity, Context,Congruence and Construct Domain) of 4 judges. Regarding content validity, it was obtained usingKMO and Bartlett’s sphericity tests. Results: (KMO = .764; P <.05) indicates that the instrument isappropriate for a confirmatory factor analysis (CFA), which suggests that the instrument must have a content distributed in 3 factors that explain 43.0% of the variance accumulated. Regarding the reliabilityof the instrument, this reached (.844) which would indicate that the instrument has adequate reliability.